Modelling the risks of foot-and-mouth disease outbreaks and assessing the effectiveness of vaccination in South Africa - Fosgate, Geoffrey Theodore (University of Pretoria, 2020)
Thesis (PhD (Veterinary Epidemiology))--University of Pretoria, 2020.